Scaling up a medium-sized company in international markets : An action research on a Finnish SaaS company in Germany - Häkkinen, Aino (My University, 2021)
Scaling is becoming increasingly relevant when discussing company growth and there is a clear need for more research on scaling up companies, especially within an international business context. It is understood that scaling is a form of company growth, however, the processes, strategies, and outcomes of scaling up have not yet been established in the literature. Software-as-a-Service (SaaS) companies have by nature great potential to be scaled up. However, previous literature on scaling up SaaS companies emphasizes the technical scalability, and the business perspective on scaling has been largely overlooked. This study contributes to the scarce stream of literature on scaling up medium-sized SaaS companies in international markets. This research aims at answering the research question on how a Finnish medium-sized SaaS company can be scaled up in Germany. The research was conducted as a qualitative action research which requires close cooperation between the researcher and the target organization. The focal company of this research is a Finnish medium-sized SaaS company that is planning on scaling up its operations in the German market. The theoretical framework of the research was derived from previous academic literature on company growth and scaling up, especially focusing on the sales and marketing perspective. Furthermore, literature on internationalization of internet-based firms was reviewed, focusing on the perspective of medium-sized SaaS companies. The empirical data was collected by interviewing three Finnish SaaS companies, observing the focal company, and interviewing two of its German customers. The findings of this research suggest that strategic allocation of resources into sales and marketing and achieving credibility by committing resources in the establishment of local presence are important when scaling up a medium-sized SaaS company in Germany. Also, the main findings suggest that the size of the SaaS company’s target customers should be acknowledged. There is a clear linkage between the findings and existing literature, and this research provides extensions to the literature. For instance, the findings of this research confirm how the intensity of the sales process contributes to the importance of personal customer contact during the sales process. Based on the findings, an action plan was created for the focal company.

Yritysten kasvuun liittyvässä keskustelussa skaalautuminen on yhä ajankohtaisempi aihe. Skaalautumiseen liittyy usein maiden rajat ylittävä liiketoiminta, minkä vuoksi skaalautumista tulisi tutkia erityisesti kansainvälisessä kontekstissa. Olennaista skaalautumisessa kasvun muotona on kustannusten ja resurssienkäytön hallinta. Ohjelmistoja palvelunomaisesti tuottavilla Software-as-a-Service (SaaS)-yrityksillä on ominaisuuksiensa puolesta potentiaalia skaalautua globaalisti toimiviksi. SaaS-yritysten skaalautumista käsittelevän kirjallisuuden painopiste on kuitenkin pitkälti teknologian skaalautumisessa ja aihetta on käsitelty liiketoiminnan näkökulmasta huomattavasti vähemmän. Tällä tutkimuksella pyrittiin täyttämään tutkimusaukkoa siitä, miten keskisuuret yritykset skaalautuvat kansainvälisillä markkinoilla. Tutkimuksessa pyrittiin vastaamaan siihen, miten keskisuuri suomalainen SaaS-yritys voidaan skaalata Saksassa. Tutkimuksen toteutustavaksi valittiin laadullinen toimintatutkimus, joka soveltuu menetelmänä käytännöllisen ongelman ratkaisuun. Tutkimuksen kohdeyritys on suomalainen keskisuuri SaaS-yritys, joka suunnittelee Saksan markkinoilla skaalautumista. Tutkimuksen teoreettinen viitekehys koostettiin aikaisemmasta yritysten kasvuun ja kansainvälistymiseen liittyvästä kirjallisuudesta keskittyen erityisesti keskisuurten SaaS-yritysten näkökulmaan. Tutkimuksessa skaalautuminen rajattiin myynnin ja markkinoinnin näkökulmaan. Tutkimuksen empiirinen aineisto kerättiin havainnoimalla kohdeyritystä sekä haastattelemalla kolmea suomalaista SaaS-yritystä ja kahta kohdeyrityksen saksalaista asiakasta. Tutkimustulosten perusteella keskeistä keskisuuren SaaS-yrityksen Saksan markkinoilla skaalautumisessa on resurssien strateginen allokointi myyntiin ja markkinointiin sekä uskottavuuden rakentaminen luomalla paikallista läsnäoloa. Lisäksi havaittiin, että SaaS-yrityksen tulee huomioida kohdemarkkinan lisäksi kohdeasiakasyritysten kokoluokka. Tutkimuksen löydökset kytkeytyvät olemassa olevaan kirjallisuuteen ja osiltaan myös täydentävät sitä. Tutkimus vahvisti aiempia löydöksiä muun muassa sen osalta, kuinka myyntiprosessin intensiivisyys edellyttää henkilökohtaista kanssakäymistä SaaS-yrityksen asiakkaiden kanssa. Löydösten perusteella kohdeyritykselle luotiin toimintasuunnitelma Saksan markkinoille skaalautumiseen.
Keywords: Scaling up,SME,SaaS,internationalization